Establishing age- and sex-specific anthropometric growth references standards for South Punjab adolescents utilizing the LMS method: findings from the Pakistani population - Long, Liu; Hamdani, Syed Danish; Hamdani, Syed Muhammad Zeeshan Haider; Zhuang, Jie; Khurram, Haris; Hadier, Syed Ghufran (Frontiers in Public Health, 2024)
The physical health of adolescents is crucial for a nation's prosperity and sustainable development. Developing specific growth standards is essential for prioritizing the well-being of Pakistan's youth. This study aims to establish normative standards for height, weight, and Body Mass Index (BMI) among 12-to 16-year-olds in South Punjab, facilitating accurate health assessments and tailored interventions.This study utilized a cross-sectional design and stratified random sampling to select 2,970 adolescents (49.73% boys and 50.26% girls) aged 12 to 16 years from South Punjab, Pakistan.Anthropometric measurements, including height, weight, and BMI, were collected. Data were stratified by age and gendersex, and smoothed percentile curves were computed using the LMS method, which incorporates the L (γ-lambda), M (µ-mu), and S (δ-sigma) parameters. Results were compared with international references to provide a comprehensive analysis.The results highlight sex-specific trends in anthropometric indicators among adolescents.Males exhibited higher mean values in height (160.50±11.50 cm), weight (45.02±9.78 kg), and BMI (17.30±2.41) compared to females (158.57±9.34 cm, 41.00±7.89 kg, and 16.29±2.82, respectively).Growth patterns indicate boys grow faster in height and weight between ages 12-14, while girls show slower annual increases. Comparative analysis with international standards reveals that boys' height and weight were generally lower than international medians (P50th), whereas girls' height was comparable or higher. BMI values for both gendersexess were lower than international norms, reflecting unique regional growth patterns.This research establishes updated age and sex-specific normative reference standards for adolescents in South Punjab, Pakistan. The study reveals that Pakistani adolescent boys exhibit higher mean values in height, weight, and BMI compared to girls, with faster growth rates between ages 12-14.Compared to international standards, Pakistani adolescents show lower BMI values, highlighting unique regional growth patterns. These standards have practical applications in screening, monitoring, and health strategy planning, contributing to efforts in promotingto promote a healthier future for the population.Future studies are recommended to utilize these local growth references for health surveillance and treatment in the local population.